The impact of chromium toxicity on the yield and quality of rice grains produced under ambient and elevated levels of CO2 - AbdElgawad, Hamada; Mohammed, Afrah E.; van Dijk, Jesper R.; Beemster, Gerrit T. S.; Alotaibi, Modhi O.; Saleh, Ahmed M. (Frontiers in Plant Science, 2023)
Rice is a highly valuable crop consumed all over the world. Soil pollution, more specifically chromium (Cr), decreases rice yield and quality. Future climate CO2 (eCO2) is known to affect the growth and yield of crops as well as the quality parameters associated with human health. However, the detailed physiological and biochemical responses induced by Cr in rice grains produced under eCO2 have not been deeply studied. Cr (200 and 400 mg Cr6+/Kg soil) inhibited rice yield and photosynthesis in Sakha 106, but to less extend in Giza 181 rice cultivar. Elevated CO2 reduced Cr accumulation and, consequently, recovered the negative impact of the higher Cr dose, mainly in Sakha 106. This could be explained by improved photosynthesis which was consistent with increased carbohydrate level and metabolism (starch synthases and amylase). Moreover, these increases provided a route for the biosynthesis of organic, amino and fatty acids. At grain quality level, eCO2 differentially mitigated Cr stress-induced reductions in minerals (e.g., P, Mg and Ca), proteins (prolamin, globulin, albumin, glutelin), unsaturated fatty acids (e.g., C20:2 and C24:1) and antioxidants (phenolics and total antioxidant capacity) in both cultivars. This study provided insights into the physiological and biochemical bases of eCO2-induced grain yield and quality of Cr-stressed rice.